Cistanche tubulosa (Schenk) Wight Extract Enhances Hindlimb Performance and Attenuates Myosin Heavy Chain IId/IIx Expression in Cast-Immobilized Mice. (22nd October 2019) - Kimbara, Yoshiyuki; Shimada, Yutaka; Kuboyama, Tomoharu; Tohda, Chihiro
Abstract : Skeletal muscle atrophy is encountered in many clinical conditions, but a pharmacological treatment has not yet been established. Cistanche tubulosa (Schenk) Wight is an herbal medicine used in traditional Japanese and Chinese medicine. In the current study, we investigated the effect of C. tubulosa extract (CTE) on atrophied muscle in vivo . We also investigated hindlimb cast immobilization in mice and devised a novel type of hindlimb-immobilizing cast, consisting of sponge-like tape and a thin plastic tube. Using this method, 3 out of 4 groups of mice ( n = 11 for each group) were cast-immobilized in the hindlimbs and administered CTE or vehicle for 13 days. A sham procedure was performed in the mice of the fourth group to which the vehicle was administered. Next, the triceps surae muscles (TS) were excised. To analyze the effect of the novel cast system and CTE administration on muscle atrophy, we evaluated TS wet weight and myofiber cross-sectional area (CSA). We also determined MyHC IId/IIx expression levels by western blotting, since their increase is a hallmark of disuse muscle atrophy, suggesting slow-to-fast myofiber type shift. Moreover, we performed two tests of hindlimb performance. The novel cast immobilization method significantly reduced TS wet weight and myofiber CSA. This was accompanied by deterioration of hindlimb function and an increase in MyHC IId/IIx expression. CTE administration did not alter TS wet weight or myofiber CSA; however, it showed a trend of amelioration of the loss of hindlimb function and of suppression of the increased MyHC IId/IIx expression in cast-immobilized mice. Our novel hindlimb cast immobilization method effectively induced muscle atrophy. CTE did not affect muscle mass, but suppressed the shift from slow to fast myofiber type in cast-immobilized mice, ameliorating hindlimb function deterioration.